A study on evolution of supply chain: from outsourcing to Collaborative Supply Chain; Myth or Reality? - Kathuria, Divya (2007)
This dissertation aims to understand the outsourcing relationships between Indian companies and the world. Outsourcing has evolved over the years from being a mere buyer-seller relationship to a collaborative supply chain partner network.